Marketing Factors and Social/Cultural Environment Influencing Decision Making in the Use of Skin-Treatment Beauty Clinic Services in Bangkok - Supatsirikul, Chunyanut; Bilmanoch, Sasiphan; Sanjit, Korakot (Siam Communication Review, 2025)
This research has three objectives: 1) to study the behavior of consumers in using beauty clinics in Bangkok, 2) to study the marketing factors that affect the decision to use beauty clinics, and 3) to study the social and cultural environments that affect consumers’ decision to use skincare clinics. This research is a quantitative research. The sample group used in the study is 400 people who have experience using beauty clinics in Bangkok. A questionnaire was used as a tool for data collection and statistics were used for data analysis, including percentage, frequency, and mean. The research results found that the majority of the sample group were female, aged 21-30 years, students with a bachelor's degree or equivalent, and an average monthly income of 15,001 - 35,000 baht. The behavior of using the beauty clinic services of the majority of the sample group aimed to care for their skin and had skin problems that they wanted to treat, such as dull skin, and used acne extraction or acne injection services the most. They mostly used the services on Saturdays and Sundays from 4:01 p.m. to 7:00 p.m., an average of 1 time per month, and spent approximately 1,001 - 3,000 baht per service. The decision to use the beauty clinic services of the majority of the sample group came from receiving information about the clinic's advertisements on social media. For the marketing factors, the top 5 most important factors for the sample group were: personnel, i.e., the treating doctor is skilled and experienced; staff who can give advice before and after using the service; physical presentation, i.e., the clinic area is clean and tidy; legal certification notices of the clinic; and quality, safe, and reliable treatment products. As for the social and cultural environment factors that influenced the decision to use the service, the top 5 factors for the sample group were: social class, which mostly considered confidence in living in society; the role of influential people on social media; family, which mostly considered total family income; information about the experiences or results of those who had used the services at that clinic; and expectations of safety from criticism in society.